Study of some biochemical parameters of vitiligo patients in Bangladesh - Amin, Md Ziaul; Rahman, Mohd Hafizur; Satter, Mohammed A (Bangladesh Journal of Scientific and Industrial Research, 2012)
This study is focus on the biochemical analysis to investigate the condition of different biochemical parameters for the Vitiligo patients. This biochemical analysis deals with the blood serum level of random blood sugar, bilirubin, urea, total protein, SGOT, SGPT, alkaline phosphatase, total cholesterol and uric acids. The increasing some of the biochemical parameters were statistically significant with the age groups. Random blood sugar analysis of the 125 patient's age group 31- 40, 41- 50 and above 50 significantly higher than the control group. No significant changes were observed in serum bilirubin, serum urea, serum creatinine, serum alkaline phosphatase (ALP) and serum asparate amino transferase (AST) level in different age group of Vitiligo patients. In this study, the serum total proteins were slightly decreased in the age group patients below 10 and 11-20 as compared to healthy controls. The average serum total protein level of the below 10 and 11-20 age group patients were 5.31 g/dl and 6.50 g/dl respectively, whereas the controls were 5.95 g/dl and 6.92 g/dl respectively. Serum cholesterol, serum triglycerides and serum uric acid levels were significantly changed in the age group 11-20 and 31-40 compared with the healthy control. The average serum cholesterol level, triglyceride (TG) level and uric acid level were 152.17 mg/dl, 90.27 mg/dl, 4.75 mg/dl and 173.40 mg/dl, 149.95 mg/dl, 5.54 mg/dl respectively for the patients of 11-20 and 31-40 years age group. The controls of these parameters for the 11-20 years and 31-40 years age groups were 150.57 mg/dl, 94.41 mg/dl, 4.28 mg/dl and 156.75 mg/dl, 101mg/dl, 4.77mg/dl respectively. These biochemical studies on Vitiligo indicated that there was no significant changed observed in some biochemical parameters in the different age group of Vitiligo patients but some biochemical parameters like total protein, total cholesterol, triglycerides (TG), uric acid and random blood sugar level were significantly changed in different age group of Vitiligo patients specially among the 11-20 and 31-40 years age group. This biochemical studies would be helpful to know details about the pathological condition of the Vitiligo patients associated with other disease. DOI: http://dx.doi.org/10.3329/bjsir.v47i2.11449 Bangladesh J. Sci. Ind. Res. 47(2), 173-186, 2012